Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1055/s-2004-821033
|View full text |Cite
|
Sign up to set email alerts
|

Verletzungen des Ringbandapparates bei Sportkletterern

Abstract: The closed traumatic rupture of finger flexor tendon pulleys in rock-climbers represents a new complex finger trauma first observed in the mid 1980s. While initially the diagnostic and therapeutic approaches varied, nowadays a standard proceeding is being applied. After clinical suspicion and eliminating the possibility of a fracture by normal radiographs, pulley strains as well as singular or multiple pulley ruptures can be diagnosed using ultrasound. If the ultrasound fails to give a definitive diagnosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…23,24 A tendon-bone distance greater than 2 mm for the A2, greater than 3.5 mm for the A3, and greater than 2 mm for the A4 pulley was defined as a pulley rupture. 22,[25][26][27] We detected C pulley injuries with ultrasound on the basis of a ruptured tendon sheath at the level of the respective pulley with local hematoma and effusion 7,28 and verified them during surgery.…”
Section: Methodsmentioning
confidence: 91%
“…23,24 A tendon-bone distance greater than 2 mm for the A2, greater than 3.5 mm for the A3, and greater than 2 mm for the A4 pulley was defined as a pulley rupture. 22,[25][26][27] We detected C pulley injuries with ultrasound on the basis of a ruptured tendon sheath at the level of the respective pulley with local hematoma and effusion 7,28 and verified them during surgery.…”
Section: Methodsmentioning
confidence: 91%
“…If there also is suspicion of an atraumatic epiphyseal fracture in the face of a negative radiograph then further evaluation through MRI is essential because early stages of epiphyseal injuries sometimes only are visible on MRI sequences. 58 -60 The MRI has proven to be highly accurate in detecting pulley injuries in many studies 15,19,31,33,34,61,62 and is accepted widely The MRI cannot directly detect the damaged pulley but the T1 sequences show the dehiscence of the tendon from the bone and the T2 sequences help to distinguish tendonitis, peritendon inflammation, intra-tendon substance lesions, and partial ruptures. Nevertheless the high cost associated with MRI inhibits its use in a universal fashion with digital injuries.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Initially a surgical repair was the primary recommendation although currently a nonsurgical approach, at least for the single rupture, has become the mainstay of treatment. 5,[13][14][15][16][17][18][19][20][21][22][23] This noninvasive approach is based on biomechanical analyses of the flexor tendon pulley system, 16,24 -29 in addition to the very good functional results of several climbers who got better by means of self therapy. 4 Several studies have shown a good to excellent outcome after conservative therapy 19 -21 and the strength deficit in the finger flexion caused by pulley rupture, which occurs initially, resolves quickly.…”
mentioning
confidence: 99%
“…Unfortunately many health professionals and researchers are reluctant to promote resistance training to improve health and well being due to their unfamiliarity with it compared to aerobic exercise [23,24] . A randomised control trial meta-analysis on the progressive introduction of resistance training on human hypertensives demonstrated that progressive resistance training reduced resting systolic and diastolic BP by ~ 2 % and 4 % respectively [55] . Resistance training as an integral part of any health programme is also vigorously promoted by the American Heart Association, the ASMC, and the US Surgeon-General ' s offi ce [23] .…”
Section: Specifi C Medical Advice For Pre-existing Health Conditions mentioning
confidence: 99%